First Experiments on Radioimmunodetection with b-12-Monoclonal Antibody Fragments against Breast Cancer Antigen - Fridrich, R.; Andres, R.; Stähli, C.; Zenklusen, H. R. (Nuklearmedizin - NuclearMedicine, 1986)
In 14 patients with breast cancer the results of radioimmunoscintigraphy with 123l-labeled b-12 monoclonal antibody fragments were correct in more than two thirds of the patients.Bei 14 Patienten mit Mammakarzinom zeigte die Radioimmunszintigraphie mit 123J markierten b-12 monoklonalen Antikörperfragmenten bei über zwei Drittel aller Patienten ein richtiges Ergebnis.